Microbial Quality and Shelf Life of Blueberry Purée Developed Using Cavitation Technology. Issue 3 (22nd February 2018) - Fan, Lihua; Martynenko, Alex; Doucette, Craig; Hughes, Timothy; Fillmore, Sherry
Abstract : Abstract: Blueberry purée was developed using hydrodynamic cavitation technology. The product was made from entire blueberries without adding any food additives. In this study, microbial reduction following each processing stage (at the industry setting) and after product pasteurization at 86, 88, 90, 92, 94, and 96 °C was investigated. Microbial quality including total plate counts, yeast and molds, and heat‐resistant molds counts was determined. Shelf life of pasteurized products stored for up to 24 weeks at room temperature were assessed for microbial quality, soluble solids (°Brix), titratable acidity (citric acid %), pH, viscosity (cP) and flow rate (cm/30 s). Our results indicated that heat‐resistant molds, initially present in frozen blueberries with counts at 2.03 log CFU/200g, were totally inactivated at 94 to 96 °C with 1 to 2 min holding time. Shelf life study showed that no product spoilage was caused by bacteria, yeasts and heat‐resistant molds along with non‐significant changes of textural characteristics. This study provided useful information for the food industry to develop variety of fruit purée products with no wastes of fruit materials. Practical Application: This study provides useful information for the food industry to develop safe liquid food products using cavitation technology without wasting any raw materials.